Inflammation Pharmacological Reaction and YMDD Mutational Patterns in Lamivudine Therapeutics Hepatitis B Virus - Liu, Hongcan; Wan, Zemin; She, Lanhui; Zhu, Yajuan; Cai, Zhiliang; Wu, Bin; Zhuang, Qizhen; Ke, Peifeng; Wu, Xinzhong; Li, Zhuo; Huang, Xianzhang (Frontiers in Pharmacology, 2021)
Background/Aims: Emergence of tyrosine-methionine-aspartate-aspartate (YMDD) motif in reverse transcriptase is a serious problem in chronic hepatitis B(CHB) patients after Lamivudine (LAM) therapy. However, relationship between inflammation pharmacological reaction and YMDD mutational patterns of CHB have not been well-characterized. The aim of this study was to investigate the inflammation pharmacological reaction and different YMDD mutants patterns of CHB patients. Methods: We investigated the inflammation pharmacological reaction and YMDD mutational patterns through biochemical, serological and virological detection in 25 YMDD mutants and 25 under detection patients , 33 CHB patients without YMDD mutants as contral group. Results: Prevalence of YMDD mutation patterns is different. Among 25 YMDD mutants patients, most were YIDD(72%),Only 16%YVDD and 12% YVDD+YVDD. The time course during the YMDD mutations were different. 52.4% patients developed mutation after LAM therapy less than 12 months. Serum hepatitis B virus (HBV) DNA levels after YMDD mutants were significantly higher than control and negative group. Serum HbsAg and HbeAg in YMDD mutants were also higher than control and negative group, but have no obviously difference in HbeAb. ALT and AST levels also showed significantly higher in mutants group. Conclusions: Illuminating inflammation pharmacological reaction and YMDD mutational patterns of CHB during pathological process may have implications for future treatment therapy in YMDD mutation patients. This may have impact on the choice of treatment strategies for lamivudine-resistant HBV.